PENINGKATAN KEMAMPUAN MOTORIK KASAR ANAK MELALUI ERMAINAN TRADISIONAL PETAK UMPET DI NAGARI KOTA KAWE PADA TAMAN KANAK-KANAK BUDI MULYA KABUPATEN SOLOK - Ratna Wilis; Vivi Anggraini; Farida Mayar; Elise Muryanti (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Stimulating gross motor development in early childhood is crucial because it impacts children’s physical, social, and emotional abilities. Observations conducted at Budi Mulya Kindergarten in Solok Regency revealed that some children still struggle with gross motor activities such as running while maintaining balance, moving quickly, and following game rules. This study involved 15 children and employed the action research (PTK) method. Planning, implementation of interventions, observation, and reflection were part of the two research cycles. To collect data, children’s activities were observed during a game of hide-and-seek. The children’s gross motor development levels were measured in each cycle using percentages. The results of the study indicate that the traditional game of hide-and-seek is capable of significantly improving children’s gross motor skills, as evidenced by improvements in their ability to run, maintain balance, move quickly, and follow game rules more effectively. Therefore, the traditional game of hide-and-seek can be used as an effective learning alternative to enhance the gross motor skills of young children while simultaneously supporting the development of their fine motor skills